Serological and molecular detection of Leptospira spp in dogs - Latosinski, Giulia Soares [UNESP]; Fornazari, Felipe [UNESP]; Babboni, Selene Daniela [UNESP]; Caffaro, Karen [UNESP]; Paes, Antonio Carlos [UNESP]; Langoni, Helio [UNESP] (Soc Brasileira Medicina Tropical, 2018)
Introduction: This study aimed to detect anti-Leptospira spp antibodies and Leptospira DNA in domestic dogs. Methods: Blood and urine from 106 dogs were evaluated by microscopic agglutination test (MAT) and polymerase chain reaction (PCR), respectively. Results: Six (5.7%) and one (1%) animals were positive by MAT and PCR, respectively. Conclusions: These results show a low prevalence of infection by Leptospira spp. The absence of positive results for the Icterohaemorrhagiae serogroup indicates the small relevance of these dogs as sources of human leptospirosis.
Keywords: Leptospirosis; PCR; Microscopic; Agglutination test